Guardian Student Thinking Process in Resolving Issues Divergence - Sri Adi Widodo; Turmudi Turmudi (Intelektual Pustaka Media Utama, 2017)
The purpose of this study was to determine the thought processes of students guardian in resolving the problem of divergence. This study included descriptive qualitative study. Instruments in the study are the researchers themselves with the help of personality tests KTS and Student Worksheet. Data collection procedures used techniques Think Out loud. Data analysis technique used to examine all the data collected, making the classification of personality types, examines the work of students in solving mathematical problems, verification of data. As for checking the validity of the data using the criteria of degree of trustworthiness. The results showed that the student's guardian do the thinking process of assimilation to the four stages of problem-solving Polya that stage to understand the problem, plan to resolve the issue, implement the plan and check the answers.